Utilization Trends of Antiviral and Antifungal Agents for Human Systemic Use in Tanzania From 2010 to 2017 Using the World Health Organization Collaborating Centre for Drug Statistics Methodology - Hamim, Hafidh; Sangeda, Raphael Z.; Bundala, Maganga; Mkumbwa, Sonia; Bitegeko, Adonis; Sillo, Hiiti B.; Fimbo, Adam M.; Chambuso, Mhina; Mbugi, Erasto V. (Frontiers in Tropical Diseases, 2021)
Introduction: The increase in antimicrobial consumption contributes to the emergence of antimicrobial resistance (AMR). Many studies have investigated the patterns of antibacterial consumption and antibacterial resistance. However, there is a paucity of data on the utilization of antivirals and antifungals in low and middle-income countries to serve as a baseline for monitoring and surveillance of AMR. This study aimed to determine systemic antifungal and antiviral utilization trends in Tanzania from 2010 to 2017, based on the Tanzania Medicines and Medical Devices Authority (TMDA) medicine importation archives. Methodology: An analytical, longitudinal retrospective survey covering 2010 to 2017 was conducted. The study utilized the Anatomical Therapeutic and Chemical (ATC) classification and Defined Daily Dose (DDD) developed by the World Health Organization (WHO) Collaborating Centre for Drug Statistics and the WHO Collaboration Centre for International Drug Consumption Monitoring. Human medicine importation data were collected from TMDA headquarters and used to assess the systemic antiviral and antifungal consumption trends. The importation data included the date, generic name, strength, brand name, currency, quantity, ATC classification, supplier country, port of entry and product supplier. The data were cleaned, reorganized and analyzed. Reference was made to the latest revised DDD list to assign antifungals and antivirals to their respective ATC/DDDs and then adjusted to the population estimates from the National Bureau of Statistics of Tanzania. Results: There was a high proportion of the use of systemic antifungals and antivirals for oral use (99.99%) than parenteral (0.01%). In regression mode, there was a significant increase in both antiviral (p-value = 0.007) and antifungal (p-value = 0.035) agents' utilization trends in Tanzania in the study period. Fluconazole had the highest proportion of utilization for antifungals, followed by ketoconazole, itraconazole and amphotericin B. For systemic antivirals, a high proportion was attributed to antiretrovirals used for HIV infections. Conclusion: Findings from this study suggest an increase in the utilization of systemic antifungal and antiviral agents. These findings may be used to further benchmark utilization and AMR studies.